Morfometri Kokon Attacus atlas Hasil Pemeliharaan di Laboratorium - Y.C Endrawati; A.M Fuah (Universitas Andalas, 2012)
Attacus atlas is one of the wild silkworms which is originated from Indonesia, which has economic value and high potency to be developed especially at the cocoon stage. These potential aspects for future developed include row material of silk fabrics, cosmetics, medical, and engineering materials. However, this potential has not been matched by productions level. Attacus atlas still live in nature with only 10% of cocoon production rate. In this study, A. atlas was reared in the laboratory to determine the different characteristics of Attacus atlas cocoon between rearing enviromntment as compared to which in nature. The results showed that the characteristics of the cocoon varies and influenced by humidity and temperature environments, place and behavior during making cocoon. Whole cocoon weight average of 6.37±1.07 g/cocoon, weight of floss (0.23±0.09 g/cocoon or 5.82±3.86%), weight of shell cocoon (0.62±0.35 g/cocoon or 11.95±3.38%), weight of pupa (3.77±1.99 g/cocoon or 71.74±9.42%), length of cocoon (54.30±5.74 mm), the diameter of the cocoon (22.26±2.60 mm posterior, 25.65±2.38 mm medial and 22.92±2.45 mm anterior), the cocoon circumference (70.42±7.48 mm posterior, 80.70±10.69 mm medial and 72.19±12.81 mm anterior).